Menilik Rezim Pengelolaan Tambang Freeport Dalam Mewujudkan Kesejahteraan Rakyat: Perpanjangan Kontrak Karya Atau Peralihan Ke Rezim Perizinan? - Yurista, Ananda Prima; Widyaningtyas, Rizky Septiana; Hasani, Alda Awwalil (Jurnal Hukum & Pembangunan, 2020)
The management of mineral and coal mining by Freeport has been carried out since 1967 based on a work agreement/contract of work, which is regulated in Law No. 11 of 1967 concerning Basic Mining Provisions. Since the enactment of Law no. 4 of 2009 concerning Coal Minerals under the authority in the management of minerals and coal changed from a work agreement/contract of work to a mining business permit. This article will try to respond to opportunities for contract extension or termination of work contacts and see which regimes will provide greater opportunities for the benefit of the state (in the sense of greater chance of realizing people's welfare). The provisional hypothesis of this article is that the licensing regime is more appropriate to be the basis for implementing the management of mineral and coal mining.